Structure elucidation of four steroids from the soft coral Sinularia nanolobata - Ngoc, Ninh Thi; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thung, Do Cong; Minh, Chau Van (Vietnam Journal of Science and Technology, 2017)
Four steroids namely 3β-hydroxyergosta-5,24(28)-diene-7-one (1), dissesterol (2), 16α-hydroxysarcosterol (3), and sarcophytosterol (4) were isolated form the soft coral Sinularia nanolobata using various chromatographic methods. Their structures were elucidated by detailed analysis of the 1D and 2D NMR data and comparison with the reported values.